In vivo analysis of the iris thickness by spectral domain optical coherence tomography. Issue 9 (15th April 2014) - Invernizzi, Alessandro; Cigada, Mario; Savoldi, Luisa; Cavuto, Silvio; Fontana, Luigi; Cimino, Luca
Abstract : Purpose: To assess the effectiveness of spectral domain optical coherence tomography (SD-OCT) in providing in vivo measurements of iris thickness in healthy and pathological subjects. Methods: 14 healthy volunteers and 14 patients with unilateral Fuchs' uveitis were enrolled in the study. The two groups were comparable for age, gender and race. Each subject underwent complete clinical examination and anterior segment SD-OCT imaging in both eyes. SD-OCT scans of the iris were performed following a cross-sectional pattern. Iris thickness values were obtained using a purposely developed software-based analysis of OCT images. Measurements were carried out twice by two trained independent operators to assess intraobserver and interobserver repeatability. Analysis of iris thickness was conducted in four main quadrants: superior, inferior, nasal and temporal. Iris thickness values from normal subjects were compared with the ones measured in the affected and fellow eyes of patients with Fuchs' uveitis. Results: Iris thickness measurements showed good intraobserver and interobserver repeatability (intraclass correlation coefficient >0.971). Superior and temporal iris sectors showed respectively thickest and thinnest values in all groups. In healthy eyes, iris thickness ranged from 327.92±37.29 μm temporally to 405.25±48.49 μm superiorly. Iris thickness measurements in the affected eyes of Fuchs' uveitis patients ranged from 285.48±56.02 μm temporally to 376.12±60.97 μm superiorly. Multiple comparison analysis showed iris thickness values to be significantly lower in eyes affected by Fuchs' uveitis than both in fellow eyes (p<0.001) of the same patients and in healthy eyes (p=0.0074). Conclusions: SD-OCT is a suitable technique for iris thickness assessment. Thickness analysis must be carried out using a sectorial approach, taking into consideration anatomical variations existing between different iris regions. SD-OCT is a potentially useful tool for detecting iris thickness variations induced by pathological conditions such as Fuchs' uveitis.